2012
DOI: 10.1093/icvts/ivs265
|View full text |Cite
|
Sign up to set email alerts
|

Repair of isolated aortic coarctation over two decades: impact of surgical approach and associated arch hypoplasia

Abstract: OBJECTIVES: A variety of surgical approaches and techniques are used for isolated coarctation repair. We have retrospectively reviewed our results of isolated repair of coarctation over the last 20 years, to establish whether the approach affects clinical outcome and the need for re-intervention. METHODS:Two hundred and eighty-eight patients who underwent isolated repair for coarctation of the aorta at Birmingham Children's Hospital between 1991 and 2010 were enrolled in this study. Chart review and the Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
2
22
0
4
Order By: Relevance
“…Por el contrario, aunque la cirugía de la coartación de aorta aislada conlleva excelentes resultados a corto y largo plazo, sigue existiendo una necesidad significativa de reintervención en estos pacientes 10 .…”
Section: Discussionunclassified
“…Por el contrario, aunque la cirugía de la coartación de aorta aislada conlleva excelentes resultados a corto y largo plazo, sigue existiendo una necesidad significativa de reintervención en estos pacientes 10 .…”
Section: Discussionunclassified
“…Several surgical techniques are available, and they all associated with low rates of mortality and severe morbidity [7,28,29,30]. Nevertheless, the rate of complications differ widely depending on factors such as the time of diagnosis, the age at repair, or the severity of aortic narrowing, and it has been shown that fetal diagnosis [31], the need to repair in the neonatal period [32,33,34], and long segment aortic arch hypoplasia [6,32,33] adversely affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Гипоплазированной считается дуга, размер которой в миллиметрах меньше, чем вес ребенка в килограммах плюс один [7]. Также можно найти упоминание следующего критерия гипоплазии: диаметр аорты менее диаметра брахиоцефального ствола [8].…”
Section: доступunclassified